Fungsi Pengendalian Kepala Daerah Dalam Pelaksanaan Program Bangsaku - Poetri E Suradinata; Apolus Betaubun; Fransiskus Wuniyu (Musamus Journal of Public Administration, 2019)
In an organization the oversight function is very much needed, with good supervision can prevent the occurrence of irregularities and ensure that the implementation of the organization's activities goes according to a predetermined plan. Supervision will provide greater benefits for an organization in dealing with deviations that have occurred, because if deviations can be prevented, then large losses can be avoided so that organizational goals will be achieved in an effective and efficient manner. This research uses a descriptive qualitative method, which will describe how the supervisor function of the district head in the implementation of the Bangsaku program in Merauke Regency. The results of this study are that the Supervision Function of the District Head in the implementation of the My Community Program in the Village, has been running optimally this will have an impact on the implementation of development and the results of development that are less well felt by the community, any assistance of My Bangs funds can reach their hands, and they too involved in the implementation so that there is no suspicion or fraud faced by the villagers. The control function carried out by the district head, often descends directly into the field and participates in checking what is done by the community related to the use of my nation's funds and any funds received by community, from income, expenditure to the reporting process of the use of funds used by the community.